A child with an STK11 mutation and Sotos syndrome-like features: can STK11 mutations produce a Sotos syndrome phenocopy?. (20th September 2011) - Baynam, Gareth; Schofield, Lyn; Goldblatt, Jack
Abstract : In accordance with interrelationships between tumour predisposition and somatic overgrowth, the authors present a boy with a familial serine threonine kinase 11 (STK11) mutation and Sotos syndrome-like features. The authors suggest that, analogous to phosphatase and tensin homolog mutations, STK11 mutations may predispose to somatic overgrowth. In a minority of instances, this may result in a Sotos syndrome phenocopy. If substantiated, this observation may yield insights into both the molecular causes of tumour predisposition and overgrowth syndromes.